PENGEMBANGAN MEDIA PEMBELAJARAN CERITA BERGAMBAR EDUKASI (CETARI) BERBASIS KEARIFAN LOKAL KEDIRI KISAH PANJI LARAS PADA MATERI TEKS FIKSI KELAS V SEKOLAH DASAR - Helviana Puspita Ayuningsih; Kukuh Andri Aka; Kharisma Eka Putri (Jurnal Manajemen Pendidikan, 2026)
This study aims to determine the level of validity, practicality, and effectiveness of CETARI media based on Kediri local wisdom, the Panji Laras story, in fictional text material for fifth grade elementary school. The research method used is Research and Development (R&D) with the ADDIE model consisting of the stages of analysis, design, development, implementation, and evaluation. Data collection techniques used include observation, interviews, questionnaires, tests, and documentation. The research instruments include validation sheets from media experts and material experts, teacher and student response questionnaires, and learning outcome tests (posttests). The results of the study showed that: (1) the validity of the media obtained an average of 88%, consisting of validation from media experts of 92% and validation from material experts of 84%; (2) the practicality of the media obtained an average of 94% in limited trials and 96% in extensive trials; and (3) the effectiveness of the media was shown by classical learning completion of 100% in limited trials and 93% in extensive trials. Thus, the CETARI media based on the local wisdom of Kediri, the story of Panji Laras, is declared very valid, very practical, and effective so that it is suitable for use in learning Indonesian in fictional text material for grade V elementary schools.